Similarities and differences between Inca Garcilaso de la Vega and Felipe Guaman Poma de Ayala - Labastida, Jaime (2017)
In this article we want to understand the minds of these two Peruvian writers, who are similar and different at the same time. The theme, is without a doubt, what connects them, but this is perhaps the only coincidence. However, there is a chasm separating them because their approaches to the theme is radically different in both authors. Inca Garcilaso is an ethnic and cultural mestizo (offspring of Spaniard and Indian) whose writing comes from the Christian culture of his father in which he is surrounded. His writing and his mentality are none other than a Spanish nobleman of the Spanish Golden Age. Another difference is in the work of Guaman Poma we found the vision of a pure, ladino (Spanish-speaking Indian) and Christianized Indian who expresses himself in a strange Spanish language, embedded in the Quechua culture and language. Guaman Poma is a man of the Mythical Age and lives immersed in the economic stage we call Upper Neolithic. On the other hand, Inca Garcilaso de la Vega is a man from the Iron Age, a complete Renaissance man.